Preservation of the Forestry Biomass and Mitigation of Atmospheric CO₂ using Concept of Reserved Forestry Biomass: A Comparative Study in Crisp and Fuzzy Environments - Devi, Sapna; Kumar, Shailendra (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we have fuzzified the nonlinear mathematical model given by Devi and Mishra [1] to compare the dynamics of carbon dioxide (CO$_2$) in crisp and fuzzy environments. Reserved forestry biomass is necessary to control the dynamics of CO$_2$. Devi and Mishra [1] have studied the dynamics of CO$_2$ under a system consisting of reserved forestry biomass, unreserved forestry biomass, and human population in a crisp environment. We have analyzed the dynamics of CO$_2$ under the system consisting of reserved forestry biomass, unreserved forestry biomass, and human population in crisp and fuzzy environments. Conditions for boundedness of solutions, existence, and stabilities of equilibrium points are discussed for the fuzzified model system. We have performed numerical simulations to validate our analytical findings and to see the comparison in the dynamics of CO$_2$ between crisp and fuzzy environments. In this study, many notable differences were found in the dynamics of CO$_2$ in crisp and fuzzy environments.